'STEALING' VICTORY AT GAUGAMELA: THE MANIPULATION OF TIME IN ARRIAN'S NARRATIVE. (October 2022) - Morrison, Gary
Abstract : There are numerous historical reconstructions of the lead-up to the Battle of Gaugamela, albeit often as a short prelude to the battle itself. The focus tends to be historical reality, with the extant sources blended to produce a probable sequence of events. Such narratives have their place, but the process masks the details provided by specific sources. This article analyses Arrian's representation of events to understand his narrative better. Particular attention is paid to his chronological 'mistake', specifically the loss of a day which is usually just corrected by commentators. I suggest that this was not an error at all, but a deliberate construct. I show that Arrian manipulates 'narrative time' by using the night in order to blur historical time, and how this creates a framework within which Arrian carefully constructs his Alexander–Parmenio exchanges. The construct of the adviser, the use of night imagery, and the select use of terminology (kleptein) are utilized by Arrian in order to maintain his heroic image of Alexander and to conceal any strategies of deception.